Rising Wage Inequality in Germany - Johannes Gernandt; Friedhelm Pfeiffer (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Based on samples from the German Socio-Economic Panel (GSOEP) 1984 to 2004, this paper investigates the evolution of wages and wage inequality in Germany. Between 1984 and 1994 wages for prime age dependent male workers increased on average by 23 percent and the wage distribution in West Germany was fairly stable. Between 1994 and 2004 average wages rose by about 8 percent in West Germany and 28 percent in East Germany. In this period wage inequality for prime age dependent males, measured by the ratio of the ninetieth to tenth percentile of the wage distribution, increased from 2.1 to 2.5 in West Germany and from 2.3 to 2.9 in East Germany. In West Germany rising wage inequality has occurred mainly in the lower part of the wage distribution, whereas in East Germany wage inequality predominantly rose in the upper part of the wage distribution. In West Germany the group of workers with low tenure experienced higher increases in wage inequality.
Keywords: J21; J24; J31; 330; Tenure; skill composition; wage inequality; wage rigidity